Deformation patterns and coordination mechanisms of cross-size microchannels during thermocompression bonding process - Baishun Zhao; Fan Mo; Wangqing Wu; Bingyan Jiang; Gerhard Ziegmann (Journal of Materials Research and Technology, 2023)
High-quality bonding of microfluidic chips is essential for driving the rapid marketization of microfluidic devices. While thermocompression bonding is known for its simplicity, challenges such as high deformation and low bond strength persist. In this paper, we conducted micro-scale compression creep experiments to address the coexistence problem between low deformation and high bond strength during the thermocompression bonding process. Accurate creep models were constructed based on the experimental results, achieving an improved simulation accuracy of 95% for microchannel deformation in thermocompression bonding. Additionally, a finite element simulation model was developed to simulate microchannel deformation during the thermocompression process. To enhance bond strength and minimize microchannel deformation, we propose two methods: microchannel height compensation and cross-size microchannel coordination. Results demonstrate a remarkable 200% improvement in bond strength with reduced microchannel deformation under the same bonding conditions. The findings of this study offer valuable insights and serve as a process reference and design basis for enhancing the quality of microfluidic chip products.